HEALTH TECHNOLOGIES ASSESSSMENT- THE SECTOR OF MEDICAL DEVICES - Conceição Portela (Formifarma, LDA., 2011)
In times of resources scarcity, health technologies should be strictly financed accordingly their added value. Health technologies assessment (HTA) is the scientific methodology that is able to provide payers with evidence based information in order to optimize their decisions. This procedure is already used to evaluate medicines, and could be considered to improve value based pricing for medical devices.